Mixed methods study of medication-related decision support alerts experienced during electronic prescribing for inpatients at an English hospital - Bell, Helen (Eur J Hosp Pharm, 2019)
OBJECTIVES: Electronic prescribing and medication administration systems are being introduced in many hospitals worldwide, with varying degrees of clinical decision support including pop-up alerts. Previous research suggests that prescribers override a high proportion of alerts, but little research has been carried out in the UK. Our objective was to explore rates of alert overriding in different prescribing situations and prescribers’ perceptions around the use of decision support alerts in a UK hospital. METHODS: We conducted a mixed methods study on three cardiology wards, directly observing medical and non-medical prescribers’ alert override rates during both ward round and non-ward round prescribing; observations were followed by semi-structured interviews with prescribers, which were then transcribed and analysed thematically. RESULTS: Overall, 69% of 199 observed alerts were overridden. Alerts experienced during ward rounds were significantly more likely to be overridden than those outside of ward rounds (80% of 56 vs 51% of 63; p=0.001, Χ(2) test). While respondents acknowledged that alerts could be useful, several also described negative unintended consequences. Many were of the view that usefulness of alerts was limited if the alert was reminding them to do something they would do anyway, or suggesting something they did not feel was relevant. Findings suggest that targeting, timing and additional features of alerts are critical factors in determining whether they are acted on or overridden. CONCLUSION: The majority of alerts were overridden. Alerts may be less likely to be overridden if they are built into the prescribing workflow.